Clustering and detection of good and bad rail line anchors from images - Islam, Samiul; Khan, Rubayat Ahmed (© 2015 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in the International Conference on Computer and Information Technology, ICCIT 2015; Military Institute of Science and Technology (MIST)Mirpur CantonmentDhaka; Bangladesh; 21 December 2015 through 23 December 2015 [© 2015 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICCITechn.2015.7488072